The Influence Of Project-Based Learning On Concept Mastery, Self-Efficacy, And Student Collaboration In Grade Vii At Xyz Junior High School, West Jakarta - Endah Dwi Pramusinta*; Suciati Suciati (Universitas Syiah Kuala, 2023)
This study aims to test the effectiveness of Project-Based Learning (PjBL) model to improve concept mastery, self-efficacy, and collaboration skills for grade VII students in SMP XYZ. The data used to take from 55 students divided into two groups, namely the control group of 27 students and the experimental group consisting of 28 students. The students in the control group were given conventional learning (lecturing), while the students in the experimental group were given PjBL learning. The result of the assessment of students' concept mastery, self-efficacy, and collaboration skills were then tested using the difference test followed by the calculation of the n-gain value to determine the level of effectiveness of PjBL to improve concept mastery, self-efficacy, and collaboration. The result of this analysis indicates that PjBL is effective in improving concept mastery, self-efficacy, and collaboration skills. The results of different tests on concept mastery, self-efficacy, and collaboration before learning showed a significant p-value of 0.661 for concept mastery, 0.113 for self-efficacy and 0.612 for collaboration. While the different test after learning shows a significant p value of 0.000 in concept mastery and 0.024 in collaboration. In the N-Gain Score data from the results of the t-test in the experimental class and the control class shows a p-value of 0.000. The p value of the t-test on efikasi diri value data is 0.000.